Minimizing machining airtime motion with an ant colony algorithm - Abdullah, Haslina; Ramli, Rizauddin; Abd Wahab, Dzuraidah; Abu Qudeiri, Jaber (2016)
In machining operations, repositioning the cutting tool requires airtime motion of the cutting tool. Minimizing the airtime motion during pocket machining in mass production is important for increasing the efficiencies of the machining process. This paper presents an optimization of airtime motion during contour parallel offset machining by minimizing the tool retraction based on Ant Colony Optimization (ACO). Optimization of the tool retraction is modelled as an application of the Travelling Salesman Problem (TSP). To evaluate the performance of ACO, its result for the length of the non-productive tool path is compared with that of conventional computer-aided manufacturing (CAM) software. It is found that the ACO method produces a non-productive tool path length that is approximately 60% shorter than the conventional method.